2015
DOI: 10.1371/journal.pone.0135814
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera as an Anti-Cancer Agent against Breast and Colorectal Cancer Cell Lines

Abstract: In this study we investigated the anti-cancer effect of Moringa oleifera leaves, bark and seed extracts. When tested against MDA-MB-231 and HCT-8 cancer cell lines, the extracts of leaves and bark showed remarkable anti-cancer properties while surprisingly, seed extracts exhibited hardly any such properties. Cell survival was significantly low in both cells lines when treated with leaves and bark extracts. Furthermore, a striking reduction (about 70–90%) in colony formation as well as cell motility was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(146 citation statements)
references
References 42 publications
(45 reference statements)
5
111
1
6
Order By: Relevance
“…Many of the bioactive compounds isolated from M. oleifera seeds have been found to be potential antitumor promoters [46,53]. However, recent study results found that the ethanol extract of M. oleifera seeds had no significant effect in inhibiting the proliferation of breast and colorectal tumour cells [63]. Nevertheless, a recent study observed a cytotoxic effect of M. oleifera oil in several cancer cell lines [64].…”
Section: Phytochemistry and Medicinal Usesmentioning
confidence: 99%
“…Many of the bioactive compounds isolated from M. oleifera seeds have been found to be potential antitumor promoters [46,53]. However, recent study results found that the ethanol extract of M. oleifera seeds had no significant effect in inhibiting the proliferation of breast and colorectal tumour cells [63]. Nevertheless, a recent study observed a cytotoxic effect of M. oleifera oil in several cancer cell lines [64].…”
Section: Phytochemistry and Medicinal Usesmentioning
confidence: 99%
“…Using annexin V and PI dual staining techniques whereby annexin V binds to translocated phosphatidylserine (PS) on the outer surface of cell membrane caused by apoptosis and PI passes through cell membrane when the membrane integrity has been compromised due to necrosis cell death and intercalate into nucleic acid of cell cytoplasm, Al-Asmari et al showed that ethanolic extracts of M. oleifera leaves and bark induced apoptosis in MDA-MDB-231 breast cancer cells and HCT8 colorectal cancer cells while ethanolic extract of the plant seeds mildly triggered apoptosis in HCT8 cells only [59]. In addition, a potential oral anticancer drug of cold water extract of M. oleifera leaves induced apoptosis HepG2 human hepatocellular carcinoma cells by activating caspase 3 via cleavage and downregulating the expression of Bcl-xL anti-apoptotic protein [60].…”
Section: Induction Of Apoptosis By M Oleifera In Cancer Cellsmentioning
confidence: 99%
“…Naturaceuticals such as silibinin, quercetin, curcumin [13][14][15] and plant extracts such as Curcuma longa, Moringa oleifera, Camellia sinensis, Dictyopteris undulata have also been tested for their anticancer effects against colon cancer. [16][17][18][19] In previous studies C. fimbriata has been evaluated against several cancer models except colon cancer. Methanolic extract of the C. fimbriata reported to exhibit anti lung cancer activity, Priya et al carried out cell viability and growth inhibition activity of the methanolic extract of C. fimbriata against A-549 lung cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%